The Issue of Air Quality in Socio-Scientific Teaching: Does it Impact 11--13-years-old Students' Informal Reasoning Skills? - Kuswanto, ‎ Kuswanto; Abdul Somad, Momod; Nurihsan, Juntika; Restiana Sukardi, Rendi; Abidin, Yunus; Trie Kurniawan, Dede; Binti Jajuri, Titiyaka; Syahriyati, ‎ (KnE Social Sciences, 2024)
Various land transportations mostly use fossil fuels which produce greenhouse gas emissions. This is a challenge of how to teach the content to elementary school students with a socio-scientific issue approach to the theme of the water quality index. The method used was a pre-experiment with a one-group pretest-posttest design that involved 25 students aged 11–13 at one of the private schools in Bandung. The instrument used was questions of reasoning skills that asked students argumentation. Students’ reasoning skills are analyzed and classified based on the quality of their answers. The results showed that thematic teaching strategies with socio-scientific issues were able to improve the quality of students’ reasoning skills. Students’ answers were not only dominated by claims but also provided with data and evidence even though they were not found in large numbers. In the opinion of students, the packaging of thematic teaching through scientific issues on the theme of water quality index was able to attract their attention. This indicates that increasing reasoning skills can be improved by infusing socio-scientific issues into teaching themes. Keywords: socio-scientific issue, water quality index, reasoning skills.